Tinjauan Sosiologi Hukum Tentang Penegakan Hukum di Indonesia - Malaka, Zuman (Taruna Law: Journal of Law and Syariah, 2025)
Law enforcement in Indonesia is an important element in creating justice and order in society. In its implementation, law enforcement in Indonesia often faces challenges. In its implementation, law enforcement in Indonesia often faces challenges. This research uses a library method which focuses on collecting data from various written sources, such as books, journals, articles and so on that are relevant to the research. The results of the research show that the reality of law enforcement in Indonesia often shows that people in power tend to receive light sentences, while lower class people face heavy penalties even for minor violations, this reflects a law that is blunt upwards and sharp downwards. The challenges of law enforcement in Indonesia are caused by several things, such as the persistence of corruption at various levels of government and the judicial system in Indonesia. Apart from that, the "No Viral No Justice" phenomenon also shows the weak integrity of law enforcement officials. Legal sociology views that to improve this condition, legal awareness and compliance is needed in society as well as strengthening the integrity of law enforcement in Indonesia.